Persistent Müllerian duct syndrome of mixed anatomical variant (combined male and female type) with mixed germ cell tumor of left intra-abdominal testis - Manisha Mohapatra; Yerraguntla Sarma Subramanya (Wolters Kluwer Medknow Publications, 2016)
Persistent Müllerian duct syndrome (PMDS) is a rare form of internal male pseudohermaphroditism characterized by retention of Müllerian duct derivatives in a phenotypically and karyotypically male patient. Deficiency of anti-Müllerian hormone (AMH) secretion or resistance to AMH action due to defective AMH-II receptor is presumed to cause such syndrome in the majority of cases. About 158 PMDS cases have been reported so far, out of which 31 cases are associated with testicular neoplasms. Herein, we describe an interesting case of young male initially diagnosed and treated for inguinal hernia, but finally diagnosed as "PMDS of mixed anatomical variant (combined male and female type) with mixed germ cell tumor of left intra-abdominal testis" comprising components of seminoma and yolk sac tumor and treated successfully.